Eagle Strategy Based on Modified Barnacles Mating Optimization and Differential Evolution Algorithms for Solving Transient Heat Conduction Problems - Turgut, Mert Sinan; Turgut, Oguz Emrah (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Solving time-dependent heat conduction problems through a conventional solution procedure of iterative root-finding method may sometimes cause difficulties in obtaining accurate temperature distribution across the heat transfer medium. Analytical root-finding methods require good initial estimates for finding exact solutions, however locating these promising regions is some kind of a black-box process. One possible answer to this problem is to convert the root-finding equation into an optimization problem, which eliminates the exhaustive process of determining the correct initial guess. This study proposes an Eagle Strategy optimization framework based on modified mutation equations of Barnacles Mating Optimizer and Differential Evolution algorithm for solving one-dimensional transient heat conduction problems. A test suite of forty optimization benchmark problems have been solved by the proposed algorithm and the respective solution outcomes have been compared with those found by the reputed literature optimizers. Moreover, five challenging real-world constrained optimization problems have been solved to further scrutinize the effectiveness of the proposed framework. Finally, two case studies associated with a transient heat conduction problem have been solved. Results show that Eagle strategy can provide efficient and feasible results for various types of solution domains.